(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
A series of novel isoxazole-incorporated benzimidazole derivatives was synthesized and investigated for antimicrobial activity. The structures of all synthesized compounds were confirmed by means of elemental analysis, infrared spectroscopy (IR), proton nuclear magnetic resonance (1H-NMR), and liquid chromatography-mass spectrometry (LC-MS). All compounds were evaluated for antimicrobial activity cup plate method against Staphylococcus aureus, Bacillus anthracis, Pseudomonas aeruginosa, Escherchia coli, Candida albicans and Aspegillus niger. The 4d, 4f and 4j compounds showed significant activity against gram-positive and gram-negative bacteria. On the basis of the interaction energy criterion, compound 4f showed the best docking interactions equal to 7.0 kcal/mol.